The development of a stakeholder-endorsed national strategic plan for advancing pain education across Canadian physiotherapy programs. Issue 1 (31st December 2022) - Wideman, Timothy H.; Bostick, Geoffrey; Miller, Jordan; Thomas, Aliki; Bussières, André; Walton, David; Tousignant-Laflamme, Yannick; Carlesso, Lisa; Hunter, Judith; Perreault, Kadija; Shay, Barbara
ABSTRACT: Background: The Canadian Pain Task Force recently advanced an action plan calling for improved entry-level health professional pain education. However, there is little research to inform the collaboration and coordination across stakeholders that is needed for its implementation. Aims: This article reports on the development of a stakeholder-generated strategic plan to improve pain education across all Canadian physiotherapy (PT) programs. Methods: Participants included representatives from the following stakeholder groups: people living with pain ( n = 1), PT students and recent graduates ( n = 2), educators and directors from every Canadian PT program ( n = 24), and leaders of Canada's national PT professional association ( n = 2). Strategic priorities were developed through three steps: (1) stakeholder-generated data were collected and analyzed, (2) a draft strategic plan was developed and refined, and (3) stakeholder endorsement of the final plan was assessed. The project was primarily implemented online between 2016 and 2018. Results: The plan was developed through five iterative versions. Stakeholders unanimously endorsed a plan that included five priorities focusing on uptake of best evidence across (1) national PT governance groups and (2) within individual PT programs; (3) partnering with people living with pain in pain education; (4) advocacy for the PT role in pain management; and (5) advancing pain education research. Conclusion: This plan is expected to help Canadian stakeholders work toward national improvements in PT pain education and to serve as a useful template for informing collaboration on entry-level pain education within other professions and across different geographic regions.